2021
DOI: 10.3390/biom11070918
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue: Understanding the Heterogeneity of Stem Cells for Regenerative Medicine

Abstract: Adipose-derived stem cells (ASCs) have been increasingly used as a versatile source of mesenchymal stem cells (MSCs) for diverse clinical investigations. However, their applications often become complicated due to heterogeneity arising from various factors. Cellular heterogeneity can occur due to: (i) nomenclature and criteria for definition; (ii) adipose tissue depots (e.g., subcutaneous fat, visceral fat) from which ASCs are isolated; (iii) donor and inter-subject variation (age, body mass index, gender, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 91 publications
0
58
0
Order By: Relevance
“…One of them would be the expression of CD105 + in more than 95% of the cultivated cell population ( Dominiciet al., 2006 ). However, when the cultivated stem cell is derived from adipose tissue, there are different reports in the literature and a consensus has not yet been observed ( Ong et al., 2021 ). When analyzing the SVF of adipose tissue which was recently isolated, a lower CD105 + cells percentage is observed.…”
Section: Discussionmentioning
confidence: 99%
“…One of them would be the expression of CD105 + in more than 95% of the cultivated cell population ( Dominiciet al., 2006 ). However, when the cultivated stem cell is derived from adipose tissue, there are different reports in the literature and a consensus has not yet been observed ( Ong et al., 2021 ). When analyzing the SVF of adipose tissue which was recently isolated, a lower CD105 + cells percentage is observed.…”
Section: Discussionmentioning
confidence: 99%
“… 21 The International Society for Cellular Therapy sets a minimum standard of MSCs as follows: cells that are positive for the surface markers of cluster of differentiation (CD)73, CD90, CD29, and CD105, but not with CD14, CD45, CD34, CD11b, or human leukocyte antigen-DR; are plastic-adherent and fibroblast-like under standard culture conditions; and can differentiate into chondrocytes, adipocytes and osteoblasts in vitro. 22 Due to the low expression of costimulatory molecules and class II major histocompatibility complex, these pluripotent stem cells do not trigger an obvious immune response after transplantation. 22 , 23 To date, MSCs have been isolated from distinct adult tissues (eg, bone marrow, peripheral blood, adipose tissue) and neonatal tissues (eg, umbilical cord and placenta).…”
Section: Introductionmentioning
confidence: 99%
“…In their comprehensive review, Ong et al discussed the heterogeneity of human ACSs, which can potentially represent an obstacle in the translation of basic ACS research into the clinics [5]. Among other factors, the source of ASCs (e.g., subcutaneous vs. visceral fat), donor and inter-subject variations as well as details of the study design were identified as potential hurdles for translational use of ASCs.…”
mentioning
confidence: 99%